Rechtliche Entscheidungen unter Unsicherheit - Christoph Engel (Max-Planck-Projektgruppe Recht der Gemeinschaftsgüter, 2001)
– Lawyers routinely have to decide under considerable uncertainty. Those officially applying the law in force, like judges or public officials, often do not know all the facts of the case. And the legislator ought to know, understand and forecast much more than he usually does. Economics, psychology and systems and cultural theory address knowledge, ignorance and uncertainty, using sharp conceptual tools. This article explores how law might exploit the knowledge of its neighbouring disciplines. In each case, the assessment hinges upon understanding how the concept of knowledge in question differs from the legal one. If and when the open integration of a foreign concept proves unfeasible, two ways out are still worth investigating. The authorities entrusted with rule application often enjoy more latitude when tracing and selecting cases. Moreover, the legislator can step in and tune a statutory provision such that it can better exploit the generic knowledge offered by a neighbouring discipline.
Keywords: 330; Rechtsprechung; Rechtsökonomik; Sozialpsychologie; Systemtheorie; Kultursoziologie; Theorie; Entscheidung bei Unsicherheit